Telomere length is independently associated with all-cause mortality in chronic heart failure - Romaine, Simon P R; Denniff, Matthew; Codd, Veryan; Nath, Mintu; Koekemoer, Andrea; Anker, Stefan D; Cleland, John G; Filippatos, Gerasimos; Levin, Daniel; Metra, Marco; Mordi, Ify R; Ouwerkerk, Wouter; et al. (Heart (British Cardiac Society), 2022)
ObjectivePatients with heart failure have shorter mean leucocyte telomere length (LTL), a marker of biological age, compared with healthy subjects, but it is unclear whether this is of prognostic significance. We therefore sought to determine whether LTL is associated with outcomes in patients with heart failure.MethodsWe measured LTL in patients with heart failure from the BIOSTAT-CHF Index (n=2260) and BIOSTAT-CHF Tayside (n=1413) cohorts. Cox proportional hazards analyses were performed individually in each cohort and the estimates combined using meta-analysis. Our co-primary endpoints were all-cause mortality and heart failure hospitalisation.ResultsIn age-adjusted and sex-adjusted analyses, shorter LTL was associated with higher all-cause mortality in both cohorts individually and when combined (meta-analysis HR (per SD decrease in LTL)=1.16 (95% CI 1.08 to 1.24); p=2.66×10−5), an effect equivalent to that of being four years older. The association remained significant after adjustment for the BIOSTAT-CHF clinical risk score to account for known prognostic factors (HR=1.12 (95% CI 1.05 to 1.20); p=1.04×10−3). Shorter LTL was associated with both cardiovascular (HR=1.09 (95% CI 1.00 to 1.19); p=0.047) and non-cardiovascular deaths (HR=1.18 (95% CI 1.05 to 1.32); p=4.80×10−3). There was no association between LTL and heart failure hospitalisation (HR=0.99 (95% CI 0.92 to 1.07); p=0.855).ConclusionIn patients with heart failure, shorter mean LTL is independently associated with all-cause mortality.